Inducible production of nitric oxide in osteoblast-like cells and in fetal mouse bone explants is associated with suppression of osteoclastic bone resorption. - Löwik, C W (1994)
Nitric oxide (NO) has been suggested to be involved in the regulation of osteoclast activity. Since osteoblasts, through the release of various factors, are the main regulators of osteoclastic resorption, first we have investigated whether osteoblast-like cells and fetal mouse long bone explants are able to produce NO. Second, we have assessed the effect of NO on osteoclastic resorption in whole bone cultures. In this study we show that primary rat osteoblast-like cells as well as the clonal rat osteoblast-like cell line UMR-106, stimulated with IFN-gamma together with TNF-alpha and LPS, produce NO, measured as nitrite production. IL-1 alpha enhanced while TGF-beta 2 inhibited TNF-alpha + IFN-gamma + LPS-stimulated NO production in UMR-106 cells dose dependently. Both the cytokines, however, had no effect when given alone. The competitive inhibitor of NO production, NG-monomethyl-arginine (L-NMMA), and cycloheximide abolished the increase in nitrite production induced by TNF-alpha + IFN-gamma + LPS, while hydrocortisone had no effect, as previously reported for chondrocytes. Calciotropic hormones had either no effect [1,25(OH)2D3] or had a small inhibitory effect (parathyroid hormone) on stimulated NO production. Furthermore, we found that in cultured fetal mouse long bone explants the combination of TNF-alpha + IFN-gamma + LPS as well as the NO donor sodium nitroprusside could inhibit osteoclastic resorption, measured as 45Ca release. The inhibition of resorption was prevented by concurrent administration of L-NMMA. Histological evaluation revealed that the TNF-alpha + IFN-gamma + LPS-induced inhibition of 45Ca release was associated with a decrease in the number of tartrate-resistant acid phosphatase-positive osteoclasts. We propose that the NO production by osteogenic cells (osteoblasts and chondrocytes) may represent an important regulatory mechanism of osteoclastic activity especially under pathological conditions characterized by release of bone-resorbing inflammatory cytokines.